Comparison of supercritical fluid extraction and hydrodistillation method for determination of agarwood essential oil - Nor Atikah, Mat Yusoff (2011)
Gaharu or agarwood is a tree in the family Thymelaeceae. Gaharu is the occasional product of two to four spesies in the family Thymelaeaceae. Mature trees will grow up to 40 meter in height and 40 centimeter in diameter. Gaharu trees in natural forests began to produce agarwood resin at the age of 20 to 45 years, depending on the resistance of trees and tree injury response. It is also one of the most expensive natural products existing today. Gaharu is many used in perfumes, medicines, and toiletery product. The objective of the experiment is to identify the compounds of the gaharu using supercritical fluid extraction (SFE) and hydrodistillation extraction methods. Results obtained from the different instrument method were then compared to analyze the compounds. The essentials oil of gaharu was obtained by supercritical extraction of components from solid materials. This is a relatively new process. From previous experiment this process gives a better quality extract but the capital costs are high. Carbon dioxide is usually used for solvent in this process. Then, a common conventional method used to extract the essential oil from gaharu is hydrodistillation. The problems of this technique are low efficiency and acquire high and continuous heating and required long extraction time. The essential oil was extract will be analyzed by gas chromatography- flame ionization detector (GC-FID) and gas chromatography-mass spectrometry (GC-MS). The results from GC-MS and GS-FID were compared to produce composition of compound from gaharu with different method of extractions.